Incidence of microsatellite instability in endometrial cancer patients in the Singaporean population. - Lau, Sein Yan. (2013)
Introduction: HNPCC is a familial tumour which is autosomal dominantly inherited. It is caused by mutations in DNA mismatch repair genes and this increases the probability of endometrial cancer associated with HNPCC. MSI occurs when DNA mismatch repair proteins are defective and this causes alterations in microsatellite sequences which causes MSI.